The pilates gym : entrepreneurship in Spain in trying times - Vera, Dusya; Rodriguez, Antonio ([London] : SAGE, 2016)
Franc'ois and Beatriz Perez were entrepreneurs who owned a pilates gym in Madrid, Spain, in 2013, a time when Spain was greatly affected by the global financial crisis. Despite the crisis, the gym's customer base was growing significantly, so they decided that a larger location was needed. The case describes the multiple financial and bureaucratic obstacles that Franc'ois and Beatriz faced as entrepreneurs seeking to expand the gym. The case invites students to put themselves in the shoes of Franc'ois and Beatriz and come up with an action plan to further grow the pilates gym while reducing the impact of public bureaucracy on the opening and the operations of the gym.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Entrepreneurship -- Case studies